Genderlect Style dalam Komunikasi Pria dan Wanita Pada Series Layangan Putus - Novi Indah Permatasari; Umaimah Wahid; Hafied Cangara (Persepsi: Communication Journal, 2022)
AbstractThe purpose of this study was to determine the effect of position in the household on communication patterns based on gender by male and female actors at Layangan Putus series. This research is a qualitative research with a phenomenological approach and using interactive analysis. Primary data is obtained from the dialogue of Layangan Putus episode 6A and 6B. The data collection technique is to listen and record the dialogue specifically on the communication provided by the male and female main character for further anaylisis. The reason of choosing this episode is due to the peak of the conflict that occurs in this series. The data was dissected using genderlect theory by Deborah Tannen. The result of the research conducted, it is evident that men are like role as problem solver, does not like to do follow up about other people problem but did not proof that men does not like when other people have similar experience with him. Meanwhile women are more likely need support or recognition, like when someone has same live experience as her and women like to do follow up regarding others people problem. Keywords: communication pattern, gender